(3GdSff GdcHjQs - (3GdHjgbj , CHh HcQ CMeO Hf GdMSjf Hf Ydj GdHjgbj GdNQGSGfj GdTGaYj, GdHjgbj,J (B458 (3g` s
(3ChdgG (B:s
(3HGH GdJZQjH ai bjGe Gddjd s
(3BNQgG (B:s
(3HGH eG jSJMH ef EJSGY GdbHQ hCYeGbg s
(3GdfSNI ebGHdI heUMMI Ydi fSNI GdEeGe CHj YeQh Hf GdUdGM hfbd GdfGSN UhQI NW GHf GdUdGM hGdSeGYGJ KGHJI HBNQ fSNJgs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3JHUQI GdYfhGf (B:s
(3QhGjI s
Keywords: (3GdMOjK h GdeUWdMs